Fairclough’s Three Dimensions Critical Discourse Analysis of Malcolm X’s Speech at Oxford Union Debate - Diandra Parta Wisnu Dewangga; Suhartawan Budianto; Kusuma Wijaya (Gudang Jurnal Multidisiplin Ilmu, 2025)
In discourse, speech is not only considered as a linguistic phenomenon but also as a means to maintain or change power relations in society. One of the clearest examples of the use of speech in discourse to change social change occurred in The Black Civil Rights Movement from 1955 to 1968 in the United States. Based on the interest in studying Malcolm X's speech further, the thesis writer decided to analyze Malcolm X's speech at the Oxford Union Debate using Fairclough's Critical Discourse Analysis framework with a qualitative method that will focus on linguistic issues as part of social and humanitarian issues. The results of this study showed deconstruction result of Malcolm X's speech text by analyzing various linguistic features from the dimensions of text practice (including positive and negative lexical items, key terms of ideology and belief, modality, and rhetorical devices), discursive practice (including intertextuality and shared knowledge), and sociocultural (including formality and personal pronouns), then continued with a discussion of the relationship between discourse, power, and ideology and the role of Malcolm X's speech in the historical context at that time. It can be concluded that Malcolm X's speech highlights his advocacy for revolutionary justice and self-defense for oppressed black people. He also challenged the power structures of his time, opposing segregation and exposing the hypocrisy of the American and Western governments with white supremacy and colonialism behind the mask of democracy.